The role of traffic flow modeling in solving current problems of transport planning in Ukraine - Zabarylo, Pavlo; Zabarylo, Oleksiy; Korotkykh, Yulia (КНУБА, 2025)
The main current problems of the transport and planning infrastructure of Ukraine are identified. A brief description of traffic flows as an object of the street-road network is given and the main reasons for the difficulty of studying them are listed. Various transport modeling techniques are proposed for consideration as one of the ways to aid in traffic flows managing. The main software packages used today to solve various transport and planning tasks are listed, and a brief overview is given taking into account their advantages and disadvantages. Conclusions are drawn regarding further directions of research in this area for the most optimal use of modeling in issues of transport planning.
Keywords: traffic flow; simulation; street-road network; micro modelling; macro modelling